Encapsulation of Doxorubicin in Furcellaran/Chitosan Nanocapsules by Layer-by-Layer Technique for Selectively Controlled Drug Delivery - Milosavljevic, Vedran; Jamroz, Ewelina; Gagic, Milica; Haddad, Yazan; Michalkova, Hana; Balkova, Radka; Tesarova, Barbora; Moulick, Amitava; Heger, Zbynek; Richtera, Lukas; Kopel, Pavel; Adam, Vojtech (Biomacromolecules, 2020)
Minimization of drug side effects is a hallmark of advanced targeted therapy. Herein we describe the synthesis of polysaccharide-based nanocapsules prepared from furcellaran and chitosan via layer-by-layer deposition using electrostatic interaction. Using doxorubicin as a model drug, prepared nanocapsules showed excellent drug loading properties and release influence by pH and stability. Targeted delivery of doxorubicin was achieved by nanocapsule surface modification using homing peptide (seq SMSIARLC). The synthesized nanocapsules possess excellent compatibility to eukaryotic organisms. In the case of nonmalignant cells (PNT1A and HEK-293), toxicity tests revealed the absences of DNA fragmentation, apoptosis, necrosis, and also disruption of erythrocyte membranes. In contrast, results from treatment of malignant cell lines (MDA-MB-231 and PC3) indicate good anticancer effects of synthesized bionanomaterial. Internalization studies revealed the nanocapsule's ability to enter the malignant cell lines by endocytosis and triggering the apoptosis. The occurrence of apoptosis is mostly connected to the presence of ROS and inability of DNA damage reparation. Additionally, the obtained results strongly indicate that peptide modification increases the speed of nanocapsule internalization into malignant cell lines while simultaneously nonmalignant cell lines are untouched by nanocapsules highlighting the strong selectivity of the peptide.
Keywords: Doxorubicin; algináty; Toxicity Tests; Female; polyelektrolyty; Cell Line, Tumor; Hydrogen-Ion Concentration; HEK293 Cells; ženské pohlaví; hemolýza; Nanocapsules; lidé; chitosan; testy toxicity; Chitosan; Drug Liberation; Platelet Endothelial Cell Adhesion Molecule-1; HEK293 buňky; peptidy; rostlinné gumy; léky s prodlouženým účinkem; Delayed-Action Preparations; Alginates; antigeny CD31; Drug Delivery Systems; doxorubicin; nanokapsle; Hemolysis; Polyelectrolytes; lidé středního věku; lékové transportní systémy; uvolňování léčiv; koncentrace vodíkových iontů; Middle Aged; Peptides; Plant Gums; nádorové buněčné linie; Humans